Integrasi Kurikulum Salafiyah dan Modern di Pondok Pesantren Darul Amien Gembolo Banyuwangi - Tri Saputra; Fadlilatul Ashri; Juanita Nur Istiqomah Putri; Muhammad Daffa Yudra; Ahmad Ridwan (Pusat Riset dan Inovasi Nasional, 2025)
This study explores the integration of salafiyah (traditional Islamic) and modern curricula at Darul Amien Islamic Boarding School in Gembolo, Banyuwangi, in response to the challenges of Islamic education in the modern era. The research aims to describe the planning, implementation, and evaluation of curriculum integration in pesantren education management. Employing a qualitative approach with a case study method, data were collected through interviews, observation, and documentation. The findings reveal that the pesantren has successfully combined classical Islamic texts with formal school curricula into a unified system. The learning activities follow a structured level system, with regular evaluations conducted by school administrators. Challenges such as students' low motivation toward general subjects are addressed through personal mentoring and adaptive curriculum strategies. This integration improves the quality of graduates in both religious and societal competencies.